Risk Management Analysis on KKM LKF FTI UKSW Website Using ISO 31000 Framework - Denaline Prabowo; Agustinus Fritz Wijaya (Journal of Information System and Informatics, 2022)
Currently, many organizations are utilizing the results of the application of information technology in carrying out their business processes. The Satya Wacana Christian University Student Institute KKM Points Website is a website created with the aim of assisting the process of inputting student activity points. Currently, the use of the website is still not optimal, so it is necessary to do a risk management analysis. Website risk management analysis is carried out using the ISO 31000 framework with 4 stages. The research results can be used as a reference for organizations related to risk management so that the use of the website can be carried out optimally in accordance with organizational goals.